2012
DOI: 10.18060/1867
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based Spousal Communication during Deployment: Does it Increase Post-deployment Marital Satisfaction?

Abstract: The purpose of this study was to explore the question: Is a service member's post-deployment marital satisfaction correlated with frequency and mode of communication during deployment? This study used an anonymous exploratory design with a sample of 119 Operation Iraqi Freedom (OIF) or Operation Enduring Freedom (OEF) married veterans. Service members who communicated daily during deployment with their spouses had higher marital satisfaction scores than those who communicated less than once per week. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
2
18
4
Order By: Relevance
“…Traditional communication methods of phone calls and letters were used less frequently. This finding appears to differ somewhat from that of Ponder and Aguirre (), who reported that 24% of their postdeployment sample of OIF or OEF veterans identified the telephone as their primary mode of communication home and 20% identified the U.S. mail while deployed. Participants in the Ponder and Aguirre study averaged 10 years older than participants in the current study (36 vs. 26 years), and this demographic difference may contribute to differences in communication preferences between the two samples.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Traditional communication methods of phone calls and letters were used less frequently. This finding appears to differ somewhat from that of Ponder and Aguirre (), who reported that 24% of their postdeployment sample of OIF or OEF veterans identified the telephone as their primary mode of communication home and 20% identified the U.S. mail while deployed. Participants in the Ponder and Aguirre study averaged 10 years older than participants in the current study (36 vs. 26 years), and this demographic difference may contribute to differences in communication preferences between the two samples.…”
Section: Discussioncontrasting
confidence: 86%
“…Over the past several years, a number of published articles have focused directly or in part on home‐front communications from the deployed setting (American Psychological Association, ; Carter et al., ; Durham, ; Greene, Buckman, Dandeker, & Greenberg, ; Merolla, ; Ponder & Aguirre, ; Watson‐Wiens & Boss, ). The authors’ commentaries on the implications of war‐time communication advances have voiced similar themes and have been based mostly on qualitative interviews and anecdotal reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Service members deployed to Sinai in 1995 rated letters highly for showing support, exchanging general information, staying in touch, and sharing feelings (Schumm et al, 2004). Similarly, Ponder and Aguirre (2012) reported that frequency of letter writing was more predictive of postdeployment relationship satisfaction than frequency of communication by any other medium. Contrary to their hypothesis, this was even the at UNIV REGINA LIBRARY on June 4, 2016 jfi.sagepub.com Downloaded from case when comparing letters with the synchronous, media-rich webcam communication.…”
Section: Benefits and Drawbacks Of Different Communication Mediamentioning
confidence: 99%
“…Consistent communication during deployment has also been shown to ease postdeployment transitions for both partners (Rossetto, ) and service members (Ponder & Aguirre, ). These findings support the notion that consistent communication helps sustain satisfying relationships (Stafford, ).…”
Section: Short‐term Rhythms: Daily Family Interactionsmentioning
confidence: 99%